2022
DOI: 10.1111/all.15242
|View full text |Cite
|
Sign up to set email alerts
|

Alpine altitude climate treatment for severe and uncontrolled asthma: An EAACI position paper

Abstract: Currently available European Alpine Altitude Climate Treatment (AACT) programs combine the physical characteristics of altitude with the avoidance of environmental triggers in the alpine climate and a personalized multidisciplinary pulmonary rehabilitation approach. The reduced barometric pressure, oxygen pressure, and air density, the relatively low temperature and humidity, and the increased UV radiation at moderate altitude induce several physiological and immunological adaptation responses. The environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 161 publications
(454 reference statements)
3
22
0
Order By: Relevance
“…All these changes can have a positive effect on asthma. 7 Lung function represents one of the main feature for the diagnosis and the determination of asthma severity and asthma control, 2 and its improvement has been previously reported after a stay at altitude of at least 2 weeks. 8 On the other hand, to the best of our knowledge, no information is currently available in the literature about changes in respiratory function in the first week as well as no data is available for this frame of time about small airways' evaluation during a stay at altitude, even though peripheral airways impairment, as determined by oscillometry, is common also in children with well-controlled asthma.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…All these changes can have a positive effect on asthma. 7 Lung function represents one of the main feature for the diagnosis and the determination of asthma severity and asthma control, 2 and its improvement has been previously reported after a stay at altitude of at least 2 weeks. 8 On the other hand, to the best of our knowledge, no information is currently available in the literature about changes in respiratory function in the first week as well as no data is available for this frame of time about small airways' evaluation during a stay at altitude, even though peripheral airways impairment, as determined by oscillometry, is common also in children with well-controlled asthma.…”
Section: Introductionmentioning
confidence: 96%
“…Mountain climate is characterized by the reduction of the barometric pressure, air density, relative temperature, and humidity; moreover, aeroallergen burden (both pollen and Dermatophagoides) and pollution are also reduced. All these changes can have a positive effect on asthma 7 …”
Section: Introductionmentioning
confidence: 99%
“…Located at sea level, the eastern Black Sea region has high humidity from heavy rains throughout the year [ 12 ]. In a recent study, an alpine altitude climate was found to be associated with good asthma control owing to reduced aeroallergens and less air pollution [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Interventions to decrease the allergen burden can sometimes control respiratory symptoms (e.g., alpine altitude climate treatment). 7 Moreover, the recognition of the allergic triggers of these conditions can be paramount to decide on patient's life choices (place of residence, hobbies, pet keeping habit, etc.). 8 Finally, some therapeutic interventions (e.g., allergen immunotherapy (AIT) or anti-IgE treatment) are recommended by the clinical guidelines only for allergic individuals.…”
Section: Introductionmentioning
confidence: 99%